Alternative Conservative Approach for Tooth Build-Up in Patients with Special Healthcare Needs - Kakkar, Mayank; Patnaik, Vijay Rahul Markonda; Malik, Shaima; Singh, Shilpa; Planerova, Adela (International Journal of Innovative Research in Medical Science, 2021)
Purpose: The success of an artificial crown mainly depends on the biomechanical factors such as bonding capacity of cement between the crown and abutment tooth, and root strength of the abutment tooth. In this case series, we aim to provide insight on the potential use of the cast metal post and cost for patients with intellectual disabilities and severely compromised tooth structure. Material and Methods: The first patient was a 41-year old male with the chief complaint of a dislodged porcelain fused metal (PFM) crown of tooth #20 (mandibular left second bicuspid). The patient was informed about the advantages, disadvantages, and risks of each option. After further consideration and discussion with the parents and the patient, we decided to rebuild the coronal tooth structure with the cast metal post and core and prosthetic restoration with the same crown. Patient satisfaction was measured on the visual analog scale as 10/10. The second case involves a 26-year old female, who presented with a chief complaint of chronic lingering pain on tooth #9. The tooth structure was extensively damaged and un-supportive of the ferrule, therefore, it was decided to build a metal post and core instead of a fiber post. The prosthetic restoration was made with a monolithic zirconia crown and the patient was followed up twice in 6 months and graded the satisfaction as 10/10 on a visual analog scale. Results: The most common type of posts used in dentistry has been cast post and cores in the last decade which generally includes an additional laboratory stage where a custom post is prepared according to the impression taken from the prepared post space. Conclusions: Both the presented cases explain an interesting advantage of restoring a root canal treated tooth with a metal post and core system which implies that in a prefabricated post and core restored tooth failure, a metal post, and core can potentially be the treatment of choice instead of extracting the tooth.